Comparison of field results and digital simulation results of voltage-sourced converter-based FACTS controllers. - Sen, K.K (IEEE Transactions on power delivery)
This paper compares the field results of voltage-sourced converter (VSC)-based flexible alternating current transmission system (FACTS) controllers, such as static synchronous compensator (STATCOM), static synchronous series compensator (SSSC), and unified power flow controller (UPFC) with that obtained from the computer models of the FACTS controllers using an Electro Magnetic Transients Program (EMTP) simulation package. The operational results of the actual equipment include the control of the line voltage and the control of the real and reactive power flow in the line. The correlation of the results establishes the validity of the models. The protection scheme of the FACTS controllers during faults and contingencies is also described. The simulation results can be used to accurately predict the behavior of an actual controller.